Repertoires of industrial conflict in a modern city: Łódź, Central Poland 1861-1921. (2nd November 2019) - Marzec, Wiktor
ABSTRACT: This article examines the changing patterns of industrial conflict in a rapidly modernizing Eastern European city, focusing on a multi-ethnic industrial hub. I follow repertoires of contention in four crucial moments characterized by shifting scales of the geopolitical embeddedness of the city: (1) an early Luddite riot of 1861 in the Polish autonomous sub-state within the Russian Empire, (2) the first massive labor protest and the following pogrom of 1892 in the city already fully subsumed under the imperial governance, (3) a failed revolution of 1905 with a sophisticated feedback loop between party politics and street emotions, (4) mobilization practices during the German military occupation during the IWW culminating in the tram workers strike of 1917, (5) developing forms of industrial bargaining in the early Polish state after 1918. This broad picture spanning over 60 years (1861–1921) is grounded in the existing secondary literature, extensive queries of primary sources such as administration reports, court proceedings and petitions, and the analysis of political leaflets and biographical testimonies of the working class militants. Such a cross temporal comparison brings a broader outlook on the labor unrest in Russian Poland and beyond, which before was researched only in a fragmented manner.